(untitled) (Journal of Human Sciences, 2021)
The Islam succeeded in this period of history in penetrating into the African continent, in which the Islamic armies had a great role through the Islamic conquests, the caravan trade and the missionary trips for this religion, in addition to the method of dealing with Muslims with the people of the open countries in what was stipulated by the Islamic Sharia. The people and their acceptance of this religion, the region of Fezzan, which the Muslims took as a base for spreading Islam into Africa, and the conquests reached from Zuwaila to the Palace of Khawar or Kawar in Niger, and thus the open country expanded to include most of Africa. They succeeded in the Islamic conquest more than once for these areas, given that these areas quickly turn away from Islam once the Islamic army returns to Egypt, along with the desert site of Fezzan, and the absence of military garrisons to block the attacks of the Romans.